ELECTRICAL PHENOMENA IN NERVE : II. CRAB NERVE - Shanes, Abraham M. (The Rockefeller University Press, 1949)
The resting and action potentials of the leg nerves of the spider crab are reduced by procaine, cocaine, iodoacetate, KCl, and veratrine. The first three agents depress the sensitivity of the resting potential to anoxia, while the last can be shown to augment it. Glucose sustains activity and the polarized state in the absence of oxygen, an effect blocked by iodoacetate; corresponding concentrations of lactate and pyruvate are inert under most experimental conditions. DDT and veratrine both induce repetitive activity following an impulse, but only the latter does so with a marked increase in negative after-potential. The negative after-potential induced by veratrine is decreased by KCl relatively more than the spike or the resting potential. Elevation of the calcium content of the medium increases this after-potential. Neither ion appreciably alters the time constant of repolarization. The recovery is more rapid than that obtained following prolonged activity of both veratrinized and unveratrinized nerves. Repolarization following a tetanus is accelerated by an increase in the volume of solution in contact with the fibers; associated with this is an augmentation of the positive after-potential which normally follows a bout of activity. Yohimbine induces a positive after-potential following individual spikes which is depressed by an elevation of the potassium or calcium content of the medium. These observations are discussed from the standpoint of the available evidence for the involvement of potassium at the surface of the fibers as regulated by a labile permeability and metabolism. The potassium liberated by the action potential, calculated from the polarization changes, agrees closely with an available analytical figure; less direct observations are also found to be consistent with this view.